Unlocked nailing vs. interlocking nailing for winquist type I and II femoral isthmus fractures. is there a difference? - Yu, C.K.; Wong, H.Y.; Vivek, A.S.; To, B.C.S. (2008)
Interlocking intramedullary nailing is suitable for comminuted femoral isthmus fractures, but for noncomminuted fractures its benefit over unlocked nailing is debatable. This study was undertaken to compare outcomes of interlocking nailing versus unlocked intramedullary nailing in such fractures. Ninety-three cases of noncomminuted femoral isthmus fractures (Winquist I and II) treated with interlocking nailing and unlocked nailing from 1 June 2004 to 1 June 2005 were reviewed; radiological and clinical union rates, bony alignment, complication and knee function were investigated. There was no statistical significant difference with regard to union rate, implant failure, infection and fracture alignment in both study groups. Open fixation with unlocked femoral nailing is technically less demanding and requires less operating time; additionally, there is no exposure to radiation and cost of the implant is cheaper. We therefore conclude that unlocked nailing is still useful for the management of non-comminuted isthmus fractures of the femur.